"Horses for Courses"; Comment on "Translating Evidence Into Healthcare Policy and Practice: Single Versus Multi-Faceted Implementation Strategies - Is There a Simple Answer to a Complex Question?" - Joyce E. Wilkinson; Helen Frost (Kerman University of Medical Sciences, 2015)
This commentary considers the vexed question of whether or not we should be spending time and resources on using multifaceted interventions to undertake implementation of evidence in healthcare. A review of systematic reviews has suggested that simple interventions may be just as effective as those taking a multifaceted approach. Taking cognisance of the Promoting Action on Research Implementation in Health Services (PARIHS) framework this commentary takes account of the evidence, context and facilitation factors in undertaking implementation. It concludes that a 'horses for courses' approach is necessary meaning that the specific implementation approach should be selected to fit the implementation task in hand whether it be a single or multifaceted approach and reviewed on an individual basis.